Treatment of Gingival Enlargement Induced by Dental Plaque Associated with Local Factors: Case Report - González Quesada, Jorge (2020)
Dental plaque-induced gingival enlargements associated with local factors such as the use of orthodontic appliances are frequently observed in young patients, with inadequate dental biofilm control. Among the recommended therapeutics to treat this condition is the Nonsurgical phase and the surgical approach. A clinical case of a 16-year-old patient with a gingival enlargement and its respective treatment is presented.